Challenges Faced by Patients With Progressive Supranuclear Palsy and their Families. Issue 3 (4th June 2014) - Moore, Theresa; Guttman, Mark
Abstract The literature is inadequate for understanding the challenges experienced by people with PSP and their families. Therefore, the aim of this study was to understand the challenges of people with PSP and their caregivers and identify their priority need. In this qualitative study, five focus groups were conducted with people with PSP and/or their family caregivers, one group with long‐term care staff, and one with community caregivers. Data were analyzed using fundamental qualitative description. Four themes were identified: knowledge, services, research, and symptoms. Knowledge challenges were identified as the priority need, with the most common challenges in this category being lack of knowledge of PSP among community workers, physicians, patients, and family members. Service challenges involved service access and interactions with physicians, community workers, private caregivers, and long‐term care staff. Research challenges related to the lack of research and the failure of health care providers or PSP organizations to communicate research findings. Symptoms most often identified as challenging were falls, mobility, vision, mood or thinking, speech, and swallowing. Participants identified their priority need as dissemination of information about PSP. This has not been captured in previous research. This information needs to reach doctors, long‐term care staff, community workers, patients, families, and the general public. Subsequent activities to meet this need are summarized. These activities resulted in three new resources: a brochure for patients and families; an information packet for physicians; and a webinar for staff in long‐term care and community.